Use of external control arms in immune-mediated inflammatory diseases: a systematic review - Brian G Feagan; Vipul Jairath; Claire E Parker; Christopher Ma; Siddharth Singh; John K MacDonald; Joshua Chang; Alexa Zayadi; Robert Edge; Blue Neustifter; Guowei Zhong (BMJ Open)
Objectives External control arms (ECAs) provide useful comparisons in clinical trials when randomised control arms are limited or not feasible. We conducted a systematic review to summarise applications of ECAs in trials of immune-mediated inflammatory diseases (IMIDs).Design Systematic review with an appraisal of ECA source quality rated across five domains (data collection, study populations, outcome definitions, reliability and comprehensiveness of the dataset, and other potential limitations) as high, low or unclear quality.Data sources Embase, Medline and Cochrane Central Register of Controlled Trial were searched through to 12 September 2023.Eligibility criteria Eligible studies were single-arm or randomised controlled trials (RCTs) of inflammatory bowel disease, pouchitis, rheumatoid arthritis, juvenile idiopathic arthritis, ankylosing spondylitis, psoriatic arthritis, psoriasis and atopic dermatitis in which an ECA was used as the comparator.Data extraction and synthesis Two authors independently screened the search results in duplicate. The characteristics of included studies, external data source(s), outcomes and statistical methods were recorded, and the quality of the ECA data source was assessed by two independent authors.Results Forty-three studies met the inclusion criteria (inflammatory bowel disease: 16, pouchitis: 1, rheumatoid arthritis: 12, juvenile idiopathic arthritis: 1, ankylosing spondylitis: 5, psoriasis: 3, multiple indications: 4). The majority of these trials were single-arm (33/43) and enrolled adult patients (34/43). All included studies used a historical control rather than a contemporaneous ECA. In RCTs, ECAs were most often derived from the placebo arm of another RCT (6/10). In single-arm trials, historical case series were the most common ECA source (19/33). Most studies (31/43) did not employ a statistical approach to generate the ECA from historical data.Conclusions Standardised ECA methodology and reporting conventions are lacking for IMIDs trials. The establishment of ECA reporting guidelines may enhance the rigour and transparency of future research.